Critical Conditions for Studying Interleukin‐11 Signaling In Vitro and Avoiding Experimental Artefacts. Issue 9 (27th September 2021) - Viswanathan, Sivakumar; Ng, Benjamin; Widjaja, Anissa A.; Pua, Chee Jian; Tham, Nevin; Tan, Jessie; Cook, Stuart A.; Schafer, Sebastian
Abstract: Interleukin (IL) 11 is a member of the IL6 family of cytokines which require the ubiquitous gp130 receptor to activate canonical (JAK/STAT) and non‐canonical (e.g., ERK) signaling pathways. The IL11 cytokine is upregulated in a number of fibro‐inflammatory diseases and cancer, where it binds the cognate IL11 receptor alpha subunit (IL11RA) to form a hexameric IL11:IL11RA:gp130 signaling complex. The specific IL11RA receptor is highly expressed on cells of the stromal and parenchymal niche but expressed at low levels on immune cells, highly passaged cells, or transformed cell lines. Consequently, primary cells such as hepatic stellate cells, fibroblasts, and hepatocytes are ideal experimental systems to study IL11 signaling in vitro . In contrast to immortalized cell lines, primary cells better display relevant cellular physiology and pathobiology. This collection of protocols details experimental and culturing conditions for primary cells that preserve meaningful cellular states and physiological responses ex vivo in conventional 2D cell culture systems. Readouts of cellular activity are chosen carefully to capture the non‐canonical, post‐transcriptional activity of IL11 signaling. Our data suggest that cell type, cell culture conditions, passage number, concentrations of stimuli, timing, and other factors have major implications for studies of IL11 signaling. In vitro experiments with primary cell material need to be planned and executed with great caution. Otherwise, physiologically relevant mechanisms may become dysfunctional and reproducible experimental artefacts can obscure our view of true cytokine biology. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Expansion of primary human hepatic stellate cells (HSCs) and human renal proximal tubular epithelial cells (HRPTEpiCs) Basic Protocol 2 : Expansion of primary human lung fibroblasts (HLFs) Alternate Protocol 1 : Isolation and expansion of primary mouse lung fibroblasts Support Protocol 1 : Freezing and thawing of primary cells Support Protocol 2 : Operetta high‐content imaging‐based phenotyping Support Protocol 3 : Colorimetric assay of solubilized collagen Support Protocol 4 : Quantification of fibrosis marker secretion Support Protocol 5 : Western blotting studies of IL11 signaling in HSCs, HLFs, and HRPTEpiCs Basic Protocol 3 : IL11 stimulation of primary human hepatocytes Alternate Protocol 2 : IL11 stimulation of primary mouse hepatocytes Support Protocol 6 : Alanine transaminase (ALT) secretion by human and mouse hepatocytes